Potensi Besar Budidaya Ikan Sidat (Anguilla sp.) di Kecamatan Simpenan, Sukabumi - Muhamad Dzikri; Dadang Shafruddin; Eddy Supriyono (Jurnal Pusat Inovasi Masyarakat (PIM), 2020)
Eel (Anguilla sp.) is a one of fishery commodity that has a high economic value. Eel has a very promising potential to be developed in Indonesia, especially in the village of Cidadap which is a center for glass eel collectors. This is supported by the source of glass eel which is widely spread in the estuary of Pelabuhan Ratu, one of which is the Cimandiri river. This study aims to examine the ecological value and economic status from the point of view of glass eel collectors, as well as people’s interest in eel farming. The study was conducted in Cidadap village, Pelabuhan Ratu, Sukabumi in August 2019. The method used was a descriptive analysis obtained from literature, interviews, and a survey form contains of 15 set of questions. Respondents used for interviews and filling out survey forms was 10 people with the main status as glass eel collectors in Cidadap and Loji village.The Cimandiri river environment, which was used as a glass eel catchment area, has a pretty good condition, but the sanitary condition was not in proper condition proven by rubbish that has been carried by downstream water flow. Some locals make glass eel fishing their main occupation, but glass eel fisherman’s income is not fixed and seasonally dependent. Eel farming activites have great potential to be carried out in Simpenan District. Keywords: ecology, glass eel, glass eel farming,